Women and suffrage: Political satire in the municipal elections of 2016. Study of female social representations in The Clinic - Rodríguez-Pastene Vicencio, Fabiana; Messeet Divasto, Francisco (Estudios sobre el Mensaje Periodístico, 2019)
The following paper is related to the Technological Scientific Research Project DGI CSOC11-1718 "Social Representations: Women and Municipal Elections 1935-2016", Universidad de Playa Ancha. The concept of Social Representation developed by Moscovici (1979) is taken in order to determine the attributes women are represented with in politics based on the analysis of the weekly magazine, The Clinic.
Keywords: Social representation; symbolic violence; graphic humour; women